Dampak Positif Program Bimbingan Belajar Mahasiswa KKN Terhadap Penguatan Literasi Anak di Desa Parmompang Kecamatan Panyabungan Timur - Rahmat Mulyadi; Riska Putri; Nurul Hidayah; Syamsiah Depalina Siregar (Indo Publishing, 2025)
The tutoring program implemented by students of the Community Service Program (KKN) in Parmompang Village, Panyabungan Timur District, aims to improve the basic literacy skills of children, particularly reading, writing, and arithmetic. This study employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The activities were carried out over the course of one month, twice a week, using an engaging and participatory learning approach. The results indicate an increase in students’ learning motivation, self-confidence, and literacy skills, especially in mathematics. Supporting factors for the program’s success included community, teacher, and local leader support, while obstacles faced involved limited time, learning facilities, and inconsistent attendance of participants. This program has made a positive contribution to strengthening children’s literacy in Parmompang Village, and it is recommended that it be continued through the establishment of community-managed study groups, as well as collaboration between the village government, schools, and related institutions to ensure the sustainability of its benefits